Should Body Mass Index be Used as a Criteria for Selecting Patients Who are Candidates for Umbilical Hernia Repair in a Large County Health System? - Marianna Sarkissyan; Ashkan Moazzez; Ellie Hang; Junko Ozao-Choy (The American Surgeon™, 2026)
Background Body mass index thresholds are used in our county hospital system to determine patient optimization for ventral hernia repair to reduce risk of recurrence. However, no recommendations exist specifically for umbilical hernia repairs. The study objective is to determine if the current BMI threshold for ventral hernia repair can be applied to umbilical hernia repair. Methods A retrospective chart review was performed from a county-wide multi-hospital health system for umbilical hernia repairs from 2014 to 2016. Data collected included patient and hernia characteristics, comorbidities, and intraoperative findings. Patient BMIs and recurrence rates were analyzed using chi-squared test, Student’s t-test and multivariate logistic regression. Results A total of 411 patients were included; 93 (23%) patients had BMI ≥ 35. Mean age was 45 years old, and 215 (52%) were male. Recurrences were found in 30 patients (7.2%) with 13 (43%) of the recurrences undergoing reoperation. In bivariate analysis, higher BMI, older age at time of surgery, larger intraoperative defect size, and comorbidities of pulmonary disease and cirrhosis were significantly associated with recurrence. Multivariate logistic regression analysis showed that BMI ≥ 35 (OR 3.2, 95% CI: 1.2-8.6, P = 0.02) and cirrhosis (OR 16.1, 95% CI: 3.3-85.8, P < 0.001) were two independent risk factors for recurrence. Discussion This study suggests that the BMI threshold of 35 applies to umbilical hernia patients and is an independent preoperative risk factor predicting increased recurrence after umbilical hernia repair. Nonetheless, whether BMI thresholds function as an appropriate marker to determine access to surgery in our health system requires further study.